Staging China The Politics of Mass Spectacle - Schneider, Florian (Leiden University Press, 2019)
In this volume Florian Schneider shows how mass media events fit into the political, economic, and cultural developments in China. Through expert interviews and empirical studies of production backgrounds and media contents, Schneider explores the communication strategies that informed the Beijing Olympics, the Shanghai Expo, and the 60th Anniversary of the PRC. The book discusses what the implications but also the limits of these strategies might be, and it shows to what degree different actors take advantage of China's mass media events to shape political discourse. Through an in-depth engagement with theories of mass-communication and cultural governance, "Staging China" explores this vital dimension of political communication in contemporary China, providing a novel take on networked politics and legitimation.